A comparative study on the scope and quality of the sustainability reporting of the TecDAX30 companies - Avo Schönbohm; Ulrike Hoffmann (Technische Universität Kaiserslautern, Lehrstuhl für Unternehmensrechnung und Controlling, 2011)
This paper examines the current practice in sustainability reporting among the German TecDAX 30 companies on the basis of their published sustainability reports for 2009. A scoring-system has been developed with 74 indicators, based on the international Reporting Guidelines of the Global Reporting Initiative. The examination of the reports shows that nearly half of TecDAX companies did not publish any data about aspects of sustainability and most of the remaining companies did not publish meaningful and complete reports. – – Diese Studie untersucht die Nachhaltigkeitsberichterstattung der 30 deutschen Unternehmen die im TecDAX gelistet sind, basierend auf den veröffentlichten Nachhaltigkeitsberichten für das Berichtsjahr 2009. Zur Evaluierung der Berichte wurde ein Scoring-System mit 74 Indikatoren entwickelt, welches sich an den internationalen Richtlinien der Global Reporting Initiative orientiert. Die Untersuchung zeigt, dass fast die Hälfte der Unternehmen keine Informationen zum Thema Nachhaltigkeit veröffentlichten. Darüber hinaus veröffentlichten die verbleibenden Unternehmen teilweise keine aussagekräftigen und vollständigen Berichte.
Keywords: 650